KOLABORASI LINTAS SEKTOR DALAM PENDIDIKAN KESEHATAN REPRODUKSI ANAK JALANAN - Firdha Rahma Nurbadlina; Zahroh Shaluhiyah; Antono Suryoputro (Universitas Muhammadiyah Kudus, 2021)
Background: Lack of knowledge and limited access to information about reproductive health make street children vulnerable to complex reproductive health problems, one of the problems of uncontrolled reproduction is free sex, drinking alcohol, unwanted pregnancy, abortion, Sexually Transmitted Infections (STIs), HIV/AIDS.Objective: This study aims to conduct a literature study to obtain the input on improvements in dealing with reproductive health problems in street children.Methods: This research was conducted in April 2021 by conducting literature review on various research results that have been published during January 2014 to December 2020 in national and international journals and obtained 10 research journals.Results: The results of several studies to develop reproductive health on street children from various sectors illustrate that the knowledge of street children about reproductive health is still very lacking. PKPR as the basic sector in the development of reproductive health has not touched street children. The health department as a pioneer of health reproduction has also not launched a reproductive health program for them. Social services as the father of street children have not touched on his reproductive health problems, so far social services are still focusing on the social welfare of street children.Conclusion: Health as a component is no less important in the problem of street children, especially in their reproductive health. Therefore, we need cross-sector collaboration to manage reproductive health problems of street children.